VR for Vocational and Ecological Rehabilitation of Patients With Cognitive Impairment: A Survey - Emilie Hummel; Melanie Cogne; Marie Lange; Anatole Lecuyer; Florence Joly; Valerie Gouranton (IEEE, 2023)
Cognitive impairment arises from various brain injuries or diseases, such as traumatic brain injury, stroke, schizophrenia, or cancer-related cognitive impairment. Cognitive impairment can be an obstacle for patients to the return-to-work. Research suggests various interventions using technology for cognitive and vocational rehabilitation. The present work offers an overview of sixteen vocational or ecological VR-based clinical studies among patients with cognitive impairment. The objective is to analyze these studies from a VR perspective focusing on the VR apparatus and tasks, adaptivity, transferability, and immersion of the interventions. Our results highlight how a higher level of immersion could bring the participants to a deeper level of engagement and transferability, rarely assessed in current literature, and a lack of adaptivity in studies involving patients with cognitive impairments. From these considerations, we discuss the challenges of creating a standardized yet adaptive protocol and the perspectives of using immersive technologies to allow precise monitoring, personalized rehabilitation and increased commitment.